1H NMR of 5'CGCGTATATACGCG3', a duplex and a four-membered loop. - Kallick, D A (1991)
The deoxyribonucleotide 5'CGCGTATATACGCG3' was synthesized and studied by NMR methods. This short, fully palindromic duplex also forms a hairpin under certain conditions described within. As such, it is considered to be a model for cruciform formation. We show that this sequence forms a four-membered loop and a duplex in solution. The duplex is shown to be a normal, B-DNA like helix, while the hairpin is shown to be a four-membered ATAT loop.